Insights into neurosteroids and their role in women with epilepsy - Vadlamudi, Lata; Ashley, Daniel Paul; Voinescu, P. Emanuela (Frontiers in Global Women's Health, 2024)
Epilepsy, is a serious neurological condition, characterized by recurring, unprovoked seizures and affects over 50 million people worldwide. Epilepsy has an equal prevalence in males and females, and occurs throughout the life span (1). Women with epilepsy (WWE) present with unique challenges due to the cyclical fluctuation of sex steroid hormone concentrations during their life course. These shifts in sex steroid hormones and their metabolites are intricately intertwined with seizure susceptibility and affect epilepsy during the life course of women in a complex manner. Here we present a review encompassing neurosteroids – steroids that act on the brain regardless of their site of synthesis in the body; the role of neurosteroids in women with epilepsy through their life-course; exogenous neurosteroid trials; and future research directions. The focus of this review is on progesterone and its derived neurosteroids, given the extensive basic research that supports their role in modulating neuronal excitability.